2021
DOI: 10.1200/jco.2021.39.15_suppl.508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intra-tumoral (IT) SD-101 and pembrolizumab (Pb) in combination with paclitaxel (P) followed by AC in high-risk HER2-negative (HER2-) stage II/III breast cancer: Results from the I-SPY 2 trial.

Abstract: 508 Background: I-SPY 2 is a multicenter, phase 2 trial using response-adaptive randomization within molecular subtypes defined by receptor status and MammaPrint (MP) risk to evaluate novel agents as neoadjuvant therapy for women with high-risk breast cancer. SD-101 is an investigational Toll-like receptor 9 (TLR9) agonist CpG-C class oligodeoxynucleotide that stimulates the production of IFN-α and interleukin (IL)-12, functional maturation of plasmacytoid dendritic cells, and production of cytotoxic antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The possibility to combine different approaches to increase the tumor recognition and response from the immune system is also being explored. SD-101 is a synthetic oligonucleotide that binds and activates tolllike receptor 9 in DCs, thus stimulating antigen presentation and cytotoxic T cells activity [76]. The combination of NACT with pembrolizumab and SD-101 was compared with anthracycline-and taxane-based NACT in patients with HER2-negative early BC in the adaptive I-SPY2 study [35,76].…”
Section: Other Immunotherapeutic Agentsmentioning
confidence: 99%
“…The possibility to combine different approaches to increase the tumor recognition and response from the immune system is also being explored. SD-101 is a synthetic oligonucleotide that binds and activates tolllike receptor 9 in DCs, thus stimulating antigen presentation and cytotoxic T cells activity [76]. The combination of NACT with pembrolizumab and SD-101 was compared with anthracycline-and taxane-based NACT in patients with HER2-negative early BC in the adaptive I-SPY2 study [35,76].…”
Section: Other Immunotherapeutic Agentsmentioning
confidence: 99%
“…The combination of neoadjuvant SD-101 and pembrolizumab in addition to weekly paclitaxel followed by doxorubicin and cyclophosphamide was investigated in a treatment arm of the I-SPY 2 trial (NCT01042379). Results showed a non-statistically significant increase in estimated pCR rates in seventy-five patients with high-risk, HER2-negative stage II/III breast cancer (~30 patients with TNBC) 112 .…”
Section: Cytokine Gene Therapymentioning
confidence: 94%
“…In line with this, a phase II neoadjuvant clinical trial on IRX-2, a cell-derived biological with multiple active cytokine components, in combination with aPD-1 and chemotherapy in TNBC is exploring the role of cytokine-based or augmented therapy (NCT04373031). The I-SPY2 trial has reported relevant activity from the neoadjuvant combination of chemotherapy, pembrolizumab, and a TLR-9 agonist in stage II/III breast cancer, leading to an increase in pCR and RCB I outcomes at surgery ( 54 ). However, the addition of the TLR-9 agonist did not meet the prespecified threshold for graduation in I-SPY2.…”
Section: Ongoing (Neo)adjuvant Immunotherapy Research In Early Tnbc P...mentioning
confidence: 99%